Family satisfaction in the trauma and surgical intensive care unit: another important quality measure. Issue 1 (12th August 2019) - Maxim, Tom; Alvarez, Agustin; Hojberg, Yvonne; Antoku, Derek; Moneme, Chioma; Singleton, Andrew; Park, Caroline; Matsushima, Kazuhide
Abstract : Background: A growing body of research has explored patient satisfaction as one of the healthcare quality measures. To date, scarce data are available regarding family experience in the trauma and surgical intensive care unit (TSICU). The purpose of this study was to describe and analyze the results of a family satisfaction survey in the TSICU. Methods: Family members of patients at a level 1 trauma center were invited to participate in this study after 72 hours of intensive care unit stay. Participants completed a modified version of the Family Satisfaction in the Intensive Care Unit questionnaire, a validated survey measuring family satisfaction with care and decision-making. Data collection spanned from April 2016 to July 2017. Patient characteristics were compiled from the medical record. Quantitative analysis was performed using a 5-point Likert score, converted to a scale of 0 (poor) to 100 (excellent). Results: The overall response rate was 78.6%. Of the 103 family members for 88 patients, most were young (median age: 41 years) and female (75%). Language fluency was 44.6% English-only, 31.7% Spanish-only, and 23.8% bilingual. Mean summary family satisfaction scores (±SD) were 80.6±26.4 for satisfaction with care, 79.3±27.1 for satisfaction with decision-making, and 80.1±26.7 for total satisfaction. Respondents were less satisfied with the frequency of communication with physicians (70.7±27.4) and language translation (73.2±31.2). Discussion: Overall family satisfaction with the care provided to patients in the TSICU is high, although opportunities for improvement were noted in the frequency of communication between physicians and family and language translation services. Further quality improvement projects are warranted. Level of evidence: Care management study: level V.